Financial accessibility and small-medium enterprises (SMEs) in Malaysia: The role of crowdfunding and Islamic finance - Mohd Thas Thaker, M. A.; Mohd Thas Thaker, Hassanudin *; Choong, Pai Wei * (IGI Global, 2020)
One of the common problems faced by worldwide SMEs including Malaysia is accessing external financial services. Given this fact, this chapter offers a sustainable model of source of financing for Malaysian SMEs in meeting their financial need, which is known as Islamic Crowdfunding-Small and Medium Enterprises (ICSMEs) model. Authors review comprehensive literature by focusing on the issues of financial accessibility faced by Malaysian SMEs, and the existing studies relating to SMEs, crowdfunding, and Islamic finance in support to construct ICSME model. Authors discuss the modus operandi of the proposed ICSME model and offer several significances of the model.